Fatwa : keberkesanannya memerangi ajaran sesat di Malaysia - Farahwahida Mohd Yusof (Penerbit Universiti Teknologi Malaysia Press, 2011)
Issues on fatwa and its effectiveness in facing Islamic heresy and sect in Malaysia